Navigating assigned roles for asynchronous online discussions: Examining participants’ orientation using conversation analysis - Warren, Amber N. (Online Learning, 2019)
Asynchronous computer-mediated communication (CMC) tools, such as asynchronous online discussions (AODs), are widely used in higher education. Particularly for online-only classes the organization of AOD forums is of pedagogical importance, as these discussions are one of the major opportunities for participants to develop understanding of course content. This study examines participant orientations to a common AOD practice, assigning roles. The data were gathered from a graduate-level teacher education course that used forum discussion module included in Sakai. Using a conversation analytic perspective, data were examined to understand patterns in participants’ uptake of Discussion Starter and Devil’s Advocate roles in the forum. The findings demonstrate how assigning roles established a frame for participants’ understanding of course content and delimited possibilities for participation. Further, patterns of engagement related to these roles encouraged participants to distance themselves epistemically from the content of their posts. Specifically, students took up the Devil’s Advocate role in both expected and unexpected ways. While students did use this role as an opportunity to disagree with others in the forum, they also took up the role of Devil’s Advocate to pose non-critical questions as well. Pedagogical insights and the usefulness of conversation analysis as an analytical approach are discussed.